2018
DOI: 10.1186/s13046-018-0924-y
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of CLDN7 due to promoter hypermethylation is associated with human clear cell renal cell carcinoma progression and poor prognosis

Abstract: BackgroundMetastasis is the primary cause of death in renal cell carcinoma (RCC). Loss of cell-to-cell adhesion, including tight junctions (TJs) is the initial step in the process of metastasis. Claudin-7 (CLDN7) is a major component of TJs. However, the clinical significance and its regulation of kidney tumorigenesis remain poorly understood.MethodsA total of 120 fresh clear cell RCC (ccRCC) specimens and 144 primary RCC and adjacent nonmalignant renal paraffin specimens were obtained from Department of Urolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…For example, hypermethylation of the CpG shore of the Shh gene resulted in Shh loss, and inhibition of DNA methylation increased Shh expression to halt the initiation of bladder cancer at the early stage of progression [48]; DNA methylation at an enhancer of the three prime repair exonuclease 2 gene (TREX2) was linked to decreased TREX2 gene expression and protein expression, which may affect drug-induced DNA damage repair in laryngeal cancer [49]; and Epigenetic Silencing of miRNA-338-5p and miRNA-421 drived SPINK1-Positive Prostate Cancer [50]. Besides, a recent study reported that downregulation of CLDN7 due to promoter hypermethylation contributed to human ccRCC progression and poor prognosis [51], indicating DNA methylation may also play vital roles in ccRCC. However, all of above studies have focused on the effect of DNA methylation on mRNA or miRNA, and the regulation of DNA methylation on lncRNA was rarely reported.…”
Section: Discussionmentioning
confidence: 99%
“…For example, hypermethylation of the CpG shore of the Shh gene resulted in Shh loss, and inhibition of DNA methylation increased Shh expression to halt the initiation of bladder cancer at the early stage of progression [48]; DNA methylation at an enhancer of the three prime repair exonuclease 2 gene (TREX2) was linked to decreased TREX2 gene expression and protein expression, which may affect drug-induced DNA damage repair in laryngeal cancer [49]; and Epigenetic Silencing of miRNA-338-5p and miRNA-421 drived SPINK1-Positive Prostate Cancer [50]. Besides, a recent study reported that downregulation of CLDN7 due to promoter hypermethylation contributed to human ccRCC progression and poor prognosis [51], indicating DNA methylation may also play vital roles in ccRCC. However, all of above studies have focused on the effect of DNA methylation on mRNA or miRNA, and the regulation of DNA methylation on lncRNA was rarely reported.…”
Section: Discussionmentioning
confidence: 99%
“…A high level of DNMT expression leads to DNA hypermethylation and contributes to oncogenic activation [31]. Dysregulation of claudin expression has been shown to be associated with DNA hypermethylation status of the promoter region of certain genes [29,30,32,33,34]. Our data showed that DOCK1 depletion decreased DNMT1, DNMT3a, and DNMT3b, as well as global DNA methylation followed by claudin-1 up-regulation in CLBC.…”
Section: Discussionmentioning
confidence: 61%
“…Other members of the claudin family have also been reported to function as tumor suppressors. Overexpression of claudin-4 significantly reduces the invasive potential and clonogenic activity, as well as pulmonary metastasis, in human pancreatic cancer cells [28], breast cancer cells [29], and clear cell renal cell carcinoma [30]. Genes other than CLDN1 , CLDN3 , CLDN4 , CLDN7 , and ZO1 may also be coordinately regulated by DOCK1 and may contribute to tumor growth, but this remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, our data are consistent with a possible involvement of claudin-7 in ovarian cancer progression and, in the literature, the most recent publications support the pro-metastatic role of a diminished expression of claudin-7 in different type of epithelial cancers. For instance in colorectal cancer, where claudin-7 downregulation promotes the invasion and metastasis by regulating the EMT process (35), and in renal cancer, where downregulation of claudin-7 via hypermethylation of its promoter has been demonstrated and associated with metastatic features in vitro and in vivo (36).…”
Section: Discussionmentioning
confidence: 99%